(untitled) (Research, Society and Development, 2021)
Non-contingent reinforcement (NCR) is an Applied Behavior Analysis procedure based on the delivery of items or availability of preferred activities within pre-established time intervals and independently of the occurrence of target responses. Although often successfully used to reduce misbehavior, there is no consensus on which processes are involved and responsible for the behavioral changes observed. This conceptual theoretical article discusses each of the processes involved on NCR and elucidated in the first empirical studies on this matter published in the Journal of Applied Behavior Analysis (JABA) in the nineties; it also considers the contributions of studies published in JABA in the last decade in clarifying the mechanisms through which NCR suppresses responses. It is concluded that NCR effects derive from a combination of factors that need to be considered in the construction of the intervention “package” designed for each individual.